An improved two-arcs deformational theoretical model of the expansion tubes. (November 2017) - Liu, YuZhe; Qiu, XinMing; Wang, Wei; Yu, T.X.
Highlights: Considering die radius, an improved theoretical model is proposed for expansion metal tubes. Tube expansions are classified into three deformation modes, based on critical die radius. The predictions of steady compressional force and the tube radius after expansion are obtained. Predictions by current model agree well with finite element simulations and experimental data. Current model gives a more accurate prediction, within a wide range of parameters. Abstract: In this study, the theoretical model of the expansion metal tubes reported in [1] is improved by considering the die radius r die . After the critical die radius r die * decided by the tube radius-thickness ratio and the conical angle of die is introduced, the tube expansions are classified into three different deformation modes, according to the relation between actual die radius r die and the critical die radius r die * . The detailed theoretical studies of these models are given in order to extend the applicability of the proposed theoretical model. Compared with the relevant experimental and finite element results, it is validated that the current model gives a more accurate steady compressional force, within a wide range of parameters, i.e., the tube radius-thickness ratio ≥ 20, and the die conical angle α ≤ 40° Besides, the expanded tube radius could be accurately predicted, which is important in the metal tube forming. The energy absorption abilities of the expansion tubes are then optimized by taking the tube material properties and friction into consideration. Graphical abstract: